Chidamide Enhances the Cytotoxicity of Cytarabine and Sorafenib in Acute Myeloid Leukemia Cells by Modulating H3K9me3 and Autophagy Levels - Huang, He; Wenbing, Yang; Dong, Aishu; He, Zhewei; Yao, Rongxing; Guo, Wenjian (Frontiers in Oncology, 2019)
Previous studies showed that chidamide enhances the cytotoxicity of drugs in acute myeloid leukemia (AML) cells. Therefore, we examined whether chidamide enhanced the cytotoxicity of drugs in AML cells by affecting H3K9me3 and autophagy levels. AML cells (THP-1 and MV4-11 cells) were treated with chidamide, cytarabine (Ara-c), or sorafenib alone or in combination. Cell proliferation and survival rates were analyzed by MTT, flow cytometry, and Western blotting assays. The results showed that a low dose of chidamide enhanced the cytotoxicity of Ara-c or sorafenib in AML cells, decreasing proliferation and increasing apoptosis. H3K9me3 levels as assessed by Western blotting were upregulated by chidamide treatment. Chromatin immunoprecipitation sequencing, which was used to investigate potential signaling pathways, indicated that the autophagy pathway might play a role in the effects of chidamide. The level of autophagy induced in AML cells upon treatment with Ara-c or sorafenib was inhibited by chidamide, and autophagy markers (LC3, P62) were tested by Western blotting. SIRT1 messenger RNA (mRNA) and protein levels were lower in AML cells treated with Ara-c or sorafenib in combination with chidamide than those in cells treated with these drugs alone. Additionally, the Integrative Genomics Viewer results indicate that the H3K9me3 changes were related to SIRT1-binding sites. Together, these results show that chidamide enhances the cytotoxicity of two chemotherapy drugs in AML cells by increasing the H3K9me3 level and inhibiting autophagy via decreasing the expression of SIRT1. Chidamide may be a potential treatment strategy for AML in the future, especially for refractory AML patients.